Development of a Web-enabled Spatial Decision Support System (SDSS) for Prevention of Tick Borne Disease in Kuantan, Malaysia - Hamid, Kasmah (Curtin University, 2022)
Ticks are the second most common vectors of human disease after mosquitoes. They are found on many small mammal hosts and also blood-feed on humans with the risk of transmitting diseases. Considering the diseases’ risks, this study has investigated the potential for a web-enabled spatial decision support system (SDSS) to assist government decision-makers in the control, management of resources and prevention of tick borne diseases specifically in the study area of Kuantan, Malaysia.